Papel do treinamento resistido na composição corporal, indicadores de arquitetura muscular e funcionalidade de idosos - Allendorf, Diego Brum (2015)
Background : The phenomenon of aging can affect muscle mass, muscle strength and functional independence. The decline of musculoskeletal tissue interferes significantly with the functional capacity of the elderly. However, the practice of regular resistance training can prevent and / or minimize these derived functional declines of aging. Objective : to verify the association among anthropometric variables and muscle thickness, functional independence and muscle strength in older adults who practice resistance training and those still physically active, but without practicing resistance training (RT). Method : Sectional study with a comparison group, observational and not probabilistic. The sample consisted of 114 elderly divided into two groups: resistance training group (RTG): 43 elderly individuals practicing RT; physically active group (GFA): 71 elderly considered physically active. The variables were collected: sociodemographic, anthropometric, functional independence and functionality. The instruments used were inelastic tape measure, caliper, ultrasound, test and sit-ups, dynamometer strength, TUG test. The sample was adjusted for sex, age, income and education. Results : Significant differences were found with regard to sex, marital status, income and education between investigated groups (p <0.001). No significant differences were observed between the groups regarding the anthropometric variables (p> 0.05) and muscle thickness (p> 0.05). However, the GTR elderly group had a lower average travel time on the tug test (6.24 ± 0.86 seconds) compared to the GFA which averaged 11.24 ± 4.26 seconds (p = 0.035). Conclusions : TR group elderly had significantly better performance in the TUG test, which is related to less risk of falls and fractures the elderly.